Potential of bacterial culture media in biofabrication of metal nanoparticles and the therapeutic potential of the as‐synthesized nanoparticles in conjunction with artemisinin against MDA‐MB‐231 breast cancer cells. Issue 5 (15th November 2018) - Khan, Badrealam Farheen; Hamidullah; Dwivedi, Sonam; Konwar, Rituraj; Zubair, Swaleha; Owais, Mohammad
Abstract: In the recent past, various groups have proposed diverse biocompatible methods for the synthesis of metal nanoparticles (NPs). Besides culture biomass, culture supernatants (CS) are increasingly being explored for the synthesis of NPs; however, with the ever‐increasing exploration of various CS in the biofabrication of NPs, it is equally important to explore the potential of various culture media (CMs) in the synthesis of metal NPs. Considering these aspects, in the present investigation, we explore the possible applicability of various CMs in the biofabrication of metal NPs. The synthesis of NPs was primarily followed by UV/VIS spectroscopy, and, thereafter, the NPs were characterized by various physiochemical techniques, including EM, EDX, FT_IR, X‐ray diffraction, and DLS measurements, and finally, their anticancer potentialities were investigated against breast cancer. In addition, the NPs were examined in conjunction with artemisinin for therapeutic benefits against aggressive and highly metastatic MDA‐MB‐231 breast cancer cells. Cumulatively, the results of the present study collated the potentials of various bacterial CMs in the biofabrication of metal NPs and ascertained the efficacy of the as‐synthesized silver nanoparticles, especially the combinatorial entity as intriguing breast cancer therapeutics. The data of the present study plausibly assist in advancing the therapeutic applicability of the combinatorial amalgam against aggressive and highly metastatic MDA‐MB‐231 breast cancer cells. Abstract : The present research endeavor explores the potential of bacterial culture media (CM) in the biofabrication of metal nanoparticles (NPs) and, thereafter, ascertains their therapeutic potential against MDA‐MB‐231 breast cancer cells together with artemisinin.